2012
DOI: 10.1038/aps.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of lamotrigine in Chinese children with epilepsy

Abstract: Aim: To establish a population pharmacokinetics (PPK) model for lamotrigine (LTG) in Chinese children with epilepsy in order to formulate an individualized dosage guideline. Methods: LTG steady-state plasma concentration data from therapeutic drug monitoring (TDM) were collected retrospectively from 284 patients, with a total of 404 plasma drug concentrations. LTG concentrations were determined using a HPLC method. The patients were divided into 2 groups: PPK model group (n=116) and PPK valid group (n=168). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…Models describing the PK of carbamazepine (CBZ) , clobazam (CLBZ) , clonazepam (CLNZ) , lamotrigine (LMT) , levetiracetam (LVT) , oxcarbazepine (OXC) , phenobarbital (PHB) , phenytoin (PHT) , topiramate (TPM) , valproic acid (VPA) and zonisamide (ZNS) were collected from the published literature. Given the primary objective of our analysis, models were selected if covariate effects were identified for one or more AEDs and study population included >50 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Models describing the PK of carbamazepine (CBZ) , clobazam (CLBZ) , clonazepam (CLNZ) , lamotrigine (LMT) , levetiracetam (LVT) , oxcarbazepine (OXC) , phenobarbital (PHB) , phenytoin (PHT) , topiramate (TPM) , valproic acid (VPA) and zonisamide (ZNS) were collected from the published literature. Given the primary objective of our analysis, models were selected if covariate effects were identified for one or more AEDs and study population included >50 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Models describing the adult and pediatric PK of carbamazepine (CBZ), clobazam (CLBZ), clonazepam (CLNZ), lamotrigine (LMT), levetiracetam (LVT), oxcarbazepine (OXC), phenobarbital (PHB), phenytoin (PHT), topiramate (TPM), valproic acid (VPA), and zonisamide (ZNS) were collected from the published literature. Models were transcribed into the appropriate format in R v. 3.1.1, along with the parameter estimates and combined with analytical solutions of the mathematical equations describing the concentration over time profiles (Eqs.…”
Section: Methodsmentioning
confidence: 99%
“…Salem et al [16] reviewed 145 reports of drug interactions and suggested that interactions were more severe in children under 2 years old than in adults. Unfortunately, there have only been a few investigations of the pharmacokinetics of LTG in pediatric patients [1,3,6,7,10,14] and its plasma concentration profile in children less than 3 years old is unknown.…”
Section: Introductionmentioning
confidence: 99%